Impact of Culturally Relevant Phonics Instruction on Early Literacy Acquisition among Grade 1 Learners in a Pacific Island Context - Kaito Tabakea; Tebwena Aanuri; Tiribo Baire (PT. Intelektiva Global Nusantara, 2025)
This study investigated the effects of Culturally Relevant Phonics Instruction (CRPI) on early literacy acquisition among Grade 1 learners in a Pacific Island context. Employing a quasi-experimental pretest–posttest control design over twelve weeks, the study involved 56 students assigned to an experimental and a control group. The experimental group received phonics instruction integrated with local stories, culturally familiar vocabulary, and visual imagery, while the control group followed the national phonics curriculum. ANCOVA results indicated statistically significant improvements in letter–sound recognition, decoding accuracy, and reading comprehension for students receiving CRPI, with large effect sizes across all measures. Qualitative evidence from classroom observations and teacher interviews corroborated these findings, revealing heightened student engagement, more effective phonological transfer through language bridging, and increased teacher instructional confidence. Overall, the findings demonstrate that embedding phonics instruction within learners’ linguistic and cultural contexts enhances early literacy development and supports inclusive and equitable education aligned with Sustainable Development Goal (SDG) 4.